2018
DOI: 10.1007/s11274-017-2406-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and evaluation of antimicrobial and cytotoxic activities of biogenic silver nanoparticles synthesized from Streptomyces xinghaiensis OF1 strain

Abstract: We report synthesis of silver nanoparticles (AgNPs) from Streptomyces xinghaiensis OF1 strain, which were characterised by UV–Vis and Fourier transform infrared spectroscopy, Zeta sizer, Nano tracking analyser, and Transmission electron microscopy. The antimicrobial activity of AgNPs alone, and in combination with antibiotics was evaluated against bacteria, namely Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis, and yeasts viz., Candida albicans and Malassezia furfur by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
109
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(132 citation statements)
references
References 54 publications
19
109
4
Order By: Relevance
“…Preliminary assays showed that the synthesized AgNPs displayed antimicrobial activity against P. aeruginosa. The minimal inhibitory concentration (MIC) of AgNPs was 10 µg/mL, which is comparable to values reported by similar studies for the same bacterium(4244). However, when the AgNPs were exposed to light the MIC dropped to 5 µg/mL.…”
Section: Resultssupporting
confidence: 84%
“…Preliminary assays showed that the synthesized AgNPs displayed antimicrobial activity against P. aeruginosa. The minimal inhibitory concentration (MIC) of AgNPs was 10 µg/mL, which is comparable to values reported by similar studies for the same bacterium(4244). However, when the AgNPs were exposed to light the MIC dropped to 5 µg/mL.…”
Section: Resultssupporting
confidence: 84%
“…Although AgNPs cytotoxicity has been found in several studies [14,[66][67][68][69], the molecular mechanisms involved are not completely understood [16]. AgNPs may trigger oxidative stress by reactive oxygen species (ROS) production [70,71] causing a variety of intracellular responses and alterations in antioxidant systems [72], which nally could lead to apoptosis or necrosis [73].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, silver ions, as a secondary oxidation process of AgNPs, contribute to the biocidal properties of AgNPs by affecting the transport and release of potassium (K + ) ions from the microbial cells [43]. The increase in membrane permeability may lead to more pronounced effects such as loss by leakage of cellular contents, including ions, proteins, reducing sugars and ometimes cellular energy reservoir (ATP) [49].…”
Section: Bactericidal Activitymentioning
confidence: 99%